Development of a high sensitivity MEMS accelerometer for bipedal robots - Manglicmot, Lester Ryan G.
MEMS accelerometers have various applications such as seismic activities monitoring, automotives, aerospace navigation systems and other inertial sensing applications. In particular, accelerometers together with gyroscopes are used for motion sensing of bipedal robots. High sensitivity capacitive MEMS accelerometers were developed for the enhancement of static and dynamic performance of bipedal robots. High sensitivity capacitive accelerometers are capable of differentiating very small signals from noise and measuring low amplitude vibrations hence, improving the inertial sensing of bipedal robots. These accelerometers will be integrated to an inertial measurement unit to provide better attitude estimation of the YICAL Leg II. This paper describes the design of a high sensitivity capacitive MEMS accelerometer which was compliant for MEMSCAP PolyMUMPS process and ready for fabrication. The structure was designed to have a high mechanical sensitivity of at least 40 nm/G and a differential capacitance sensitivity of not lower than 4fF/G. The accelerometer prototypes were found to have a shock survivability of at least 10 G.